Design Thinking-based Learning Assessment Guidelines to Improve Students’ Independent Learning Capability - Mahayanti, Ni Kadek Anisa; Widiana, I Wayan; Jayanta, I Nyoman Laba (Journal for Lesson and Learning Studies, 2024)
The less-than-optimal use of learning assessment, which influences the decline in independent learning abilities, is the background of this research. This study aims to develop design thinking-based learning assessment guidelines that are valid, practical and effective for improving independent learning abilities. This type of research is development research, and the research model used in this research is the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this research consisted of 4 experts, 1 teacher and 38 sixth-grade elementary school students. The object of this research test is the independent learning ability of fourth-grade elementary school students. This research implies that the learning assessment guide makes it easier for teachers to involve students in achieving learning outcomes and goals. Development of a learning assessment guide based on design thinking, especially to improve the independent learning abilities of fourth-grade elementary school students. This guide facilitates learning that encourages grade IV students to become independent learners by combining design thinking concepts in the development process. The data collection method used was a questionnaire. The implication of this research is to increase learning independence. By emphasizing learning design that encourages student initiative and responsibility for their learning process, design thinking can help increase learning independence. The research results show that the data obtained is significant, which means this assessment effectively improves the independent learning abilities of fourth-grade elementary school students.